STUDI FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI BOS TAHUN 2011 DI SMP AL AZHAR 14, SMP 12 DAN SMP 29 KOTA SEMARANG - Winastuti, Ragil Septiana; Marom, Aufarul; Hanani, Retna (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
School Operational Assistance Program (BOS) is a very important program to support education funding. This study aims to determine the BOS program implementation and to identify factors that support or hinder the implementation. This study uses a descriptive qualitative method. Data collection is done by documentation and interview with a number of informants. Data analysis is implemented through data reduction, data presentation, and verification.Phenomenon is approached by a model study of public policy implementation by George Edward III in which the factors that support and hinder the implementation are; communication, resources, disposition, and bureaucratic structure. There are factors that support and hinder the implementation of BOS in Semarang. This is due to the unfavorable socialization, the lack resources and the lack of competence to handle the policy. In addition there is also additional organizations involved in the implementation of BOS